Late adolescents' own and assumed parental preferences towards health-care related confidentiality and consent in Belgium. - David De Coninck (Public Library of Science (PLoS), 2021)
Objectives Health care professionals regularly struggle with issues relating to confidentiality and consent for physical and/or mental health issues among adolescents. We investigate late adolescents' own and assumed parental preferences towards health-care related confidentiality and consent. Methods We analyzed online survey data of four vignettes from 463 first-year university students at KU Leuven (Flanders, Belgium). We used paired samples t-tests to assess the (in)consistency between attitudes of late adolescents and their assumed parental attitudes, independent samples t-tests to estimate gender differences, and binomial logistic regressions to analyze the association of assumed parental preferences with late adolescents' own preferences. Results Attitudinal inconsistencies were present in all vignettes. Late adolescents were significantly more in favor of confidentiality and adolescent consent than what they believed their parents were. Gender differences were limited. Binomial logistic regressions indicated that assumed parental preferences were strongly associated with late adolescents' own preferences. Conclusions Findings suggest a clear difference between late adolescents' preferences and assumed parental preferences: they believe that their parents are less inclined to favor confidentiality and adolescent consent. We also find that this difference depends on the case, indicating that there is no such thing as general 'confidentiality preferences'. Rather, a decision- and/or context-specific perspective should be adopted.